SELF-EFFICACY BELIEFS AMONG SCHOOL MATHEMATICS TEACHERS OF NEPAL - Adhikari, Krishna Prasad (International Journal of Research -GRANTHAALAYAH, 2020)
Self-efficacy belief of the teacher is widely accepted construct in the professional development of the teacher. In this context, I as a mathematics teacher interested to study the efficacy beliefs of mathematics teachers in Nepal, which is a major contributing factor for teaching mathematics effectively. In this research, I, specifically, focused on exploring the self-efficacy beliefs of mathematics teachers in three aspects: student engagement, instructional strategy, and classroom management and to analyze the different contributing factors in the development of efficacy beliefs by using explanatory sequential mixed-method research. I chose 214 mathematics teachers randomly from Kathmandu district for a survey and 15 mathematics teachers from 214 mathematics teachers who participated in survey purposively for interviews. Adjusted Teacher’s Self-Efficacy Scale containing 15-items were used for survey and semi-structured interview schedule for interview. Descriptive as well as inferential statistics were used to analyze the self-efficacy beliefs of teachers and inductive approached used for the data obtained from interview. At last, I integrated both quantitative and qualitative results to deduce the findings and conclusion of the study. The result shows that teachers have good efficacy beliefs in teaching mathematics. Teachers have better efficacy beliefs in instructional strategy than in the other two. Experienced teachers have significantly higher self-efficacy beliefs than novices. Despite the huge investment of government in the teachers of public school, institutional school’s teachers have better self-efficacy beliefs in teaching mathematics. Teaching experience, teacher’s engagement in professional activities, mathematical and pedagogical content knowledge, and working environment of the school are major contributing factors in the development of the self-efficacy beliefs in mathematics teachers. There are so many factors in the development of self-efficacy of mathematics besides professional training, so stakeholders should focus on other aspects as well.